2009
DOI: 10.1016/j.jtcvs.2009.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Costs of excessive postoperative hemorrhage in cardiac surgery

Abstract: The average hospital costs related to excessive postoperative hemorrhage in cardiac surgery in Germany are substantial and associated with a significant risk of postoperative complications and death. Clinical interventions that can effectively prevent or address excessive postoperative hemorrhage in cardiac surgery are likely to have substantial cost-effectiveness potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
97
1
11

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(112 citation statements)
references
References 20 publications
1
97
1
11
Order By: Relevance
“…Christensen et al (2009) reported in a study of OPCAB surgery with haematocrit 41.86±8.35%, platelet count 206852±76272/cu mm. These findings were nearly similar to our study.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Christensen et al (2009) reported in a study of OPCAB surgery with haematocrit 41.86±8.35%, platelet count 206852±76272/cu mm. These findings were nearly similar to our study.…”
Section: Discussionmentioning
confidence: 91%
“…In 1975, the incidence of IHD in Bangladesh was reported to be 3.3 per thousand (Christensen et al, 2009) and that in 1985 was 14 per thousand (Brown et al, 2007). According to the latest WHO data published in April 2011 Coronary Heart Disease Deaths in Bangladesh reached 163,769 or 17.11% of total deaths and Bangladesh ranks 25 th position in the world in respect to cause of death due to coronary artery disease (Hartmann et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…There was also increased morbidity and 30 day morality was statistically notable in patients with higher output, degree of blood and blood product requirements [21,22]. …”
Section: Resultsmentioning
confidence: 99%
“…Кроме того, пере-ливание компонентов донорской крови является незави-симым фактором риска увеличения заболеваемости, смертности и послеоперационных затрат лечебного уч-реждения [24]. Послеоперационное кровотечение досто-верно увеличивает 30-дневную летальность [14] и значи-тельно ухудшает течение послеоперационного периода у кардиохирургических пациентов [15,32]. Говоря об эко-номической составляющей, следует отметить, что, по дан-ным литературы, послеоперационное кровотечение уве-личивает сроки госпитализации в среднем на 3 дня, а сто-имость лечения в среднем на 20% [47].…”
Section: кровотечение как фактор риска возникновения стернальной инфеunclassified